Pelatihan Pembelajaran Melalui Aplikasi Edukasi Quizizz Pada Guru SD Islam Rumaha 01 Ciputat - lutfi lutfi; Laily Nurmalia; Hastri Rosiyanti; Muhammad Ishaq Gery; Rikaro Ramadi; Nabila Filzah (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The ruhama islamic elementary school is a school located in the south tangerag. In the pandemic covid 19 today students and teachers at the time of learning used a fortification to visit a 4.0 church. After a survey conducted at the school and interviews turned out that the moderate growth in the process of the current use of technology, ginitially applied only to youtobe and googling has not been fully used for the inetractive media in the student process, the solution to the learning problem is to train teachers at school ruhama ciputat, Can increase the learning process in a class to be more effective and efisine in dealing with online learning in the pandemic period, and make students interesting, focusing on this activity is to give debriefing and training to a ruhama primary school teacher with the methods used are lectures, demostration and practice, and question-and-answer. At this point a ruhama primary school teacher was given information about using the media on the quizizz application asa media tool that could be used to make inetractive tests